Update-ordering for database consistency in peer-to-peer environments - Shuhadah, W. N.; Mat Deris, Mustafa Mat; Noraziah, A. N.; Saman, M. Y. M.; Rabiee, M. (IEEE, 2006)

(untitled)
Database consistency is one of the major issues in replicated database in peer to peer environment. The logical design for the replicated nodes and the transaction management mechanism are two aspects that give a serious impact to the performance and the consistency of replicated database. This paper proposes a new model that combines the Neighbor Replication on Grid (NRG), where the data is replicated to the neighbors of the grid with the Update Ordering approach. The performance comparison shows that the proposed mechanism is greatly improve the performance of the replicated database in peer to peer environment up to two orders of magnitude while preserving the data consistency.